4y(y-3) + 5 = 12(y-3) step by step solve equation 8/20/2013 | Arlandria from Miami, OK | 4 Answers | 0 Votes
6/y+4 + 1 = 5/2y+8 step by step solve the equations 8/20/2013 | Arlandria from Miami, OK | 1 Answer | 0 Votes
2x-3/x+1 = 2 - 3x-1/x+1 step by step solve equations 8/20/2013 | Arlandria from Miami, OK | 2 Answers | 0 Votes
0.1(w+0.5) +0.2w =0.2 (w-0.4) step by step solve equation 8/20/2013 | Arlandria from Miami, OK | 4 Answers | 0 Votes
0.1(t+0.5) +0.2t =0.3(t-0.4) just solve the equation step by step 8/20/2013 | Arlandria from Miami, OK | 2 Answers | 0 Votes